Improving the organizational culture of key stakeholders involved in value management process to achieve optimum value in Malaysian construciton - Chung, Meng Chan; Ibrahim, Rahinah; Abdul Ghafar, Maszura (Asian Scholars Network, 2023)
Value Management (VM) is necessary for all construction projects to achieve value for money. There is a need to improve the organizational culture of key stakeholders involved in VM process to achieve optimum value in Malaysian construction projects. This paper is part of a larger study aiming to develop a culture-based organizational model for key stakeholders involved in VM process for achieving optimum value in Malaysian construction projects. This study utilizes a systematic literature review synthesis method to evaluate the trend, identify the gaps and recommend future approach in order to improve the organizational culture of key stakeholders involved in VM process that focuses on achieving optimum value in VM. The results include analyzing current VM status quo in Malaysian construction industry, determining the challenges faced in the VM process of generating innovative ideas, and exploring the project value creation to achieve optimum value. Upon introducing the background problem, the paper deliberates the synthesized literature reviews on VM, key stakeholders, VM process and project performance with VM. A cross-analyses discussion contributes towards formulating the culture-based organizational model for VM practice in Malaysia. The results are expected to improve the integrated project delivery performance of Malaysian construction industry stakeholders by understanding critical VM success factors and weaknesses of VM key stakeholders’ team in generating innovation ideas for optimum project delivery value.